2021
DOI: 10.1007/s12032-021-01594-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cell cycle as the critical pathway modulated by exosome-derived microRNAs in gallbladder carcinoma

Abstract: Gallbladder cancer (GBC), the most common malignancy in the biliary tract, is highly lethal malignant due to seldomly specific symptoms in the early stage of GBC. This study aimed to identify exosome-derived miRNAs mediated competing endogenous RNAs (ceRNA) participant in GBC tumorigenesis. A total of 159 differentially expressed miRNAs (DEMs) was identified as exosome-derived miRNAs, contains 34 upregulated exo-DEMs and 125 downregulated exo-DEMs based on the expression profiles in GBC clinical samples downlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Moreover, STEAP3-AS1 caused the expression of its neighboring STEAP3 in a m 6 A modification-dependent manner, which activated Wnt/β-catenin signaling to support CRC progression. Importantly, recent in silico analysis of a serum exosome-derived ceRNA network has identified STEAP3-AS1 as an independent prognostic predictor of glioblastoma and gallbladder cancer [ 48 , 49 ], further proving its clinic value as a promising biomarker for cancers. Therefore, further studies elucidating the functions of secreted STEAP3-AS1 in CRC progression may expand its applications for early detection or prediction of drug response in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, STEAP3-AS1 caused the expression of its neighboring STEAP3 in a m 6 A modification-dependent manner, which activated Wnt/β-catenin signaling to support CRC progression. Importantly, recent in silico analysis of a serum exosome-derived ceRNA network has identified STEAP3-AS1 as an independent prognostic predictor of glioblastoma and gallbladder cancer [ 48 , 49 ], further proving its clinic value as a promising biomarker for cancers. Therefore, further studies elucidating the functions of secreted STEAP3-AS1 in CRC progression may expand its applications for early detection or prediction of drug response in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests a potential role of hsa-miR-4647 as a messenger in the tumor microenvironment. A recent study revealed hsa-miR-4647 was one of two significantly upregulated miRNAs in gallbladder carcinoma and associated with patients’ unfavorable prognosis [36] , suggesting hsa-miR-4647 could be a promising target for developing novel treatment modality for gallbladder carcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al recently demonstrated that the analysis of miRNA targets from exosomes (i.e., purified from urine), when compared with traditional TaqMan qPCR technology, was significantly more accurate and sensitive for the detection of low concentrations (i.e., <100 copies/µL) [ 316 ]. However, although Bio-Rad offers a large array of mRNA-based detection using their ddPCR instrument, they have not established a standardized protocol for the analysis of miRNAs, and the only available protocols are from published studies [ 317 , 318 ]. The protocol of Hindson et al suggests that using ddPCR with TaqMan probes improved the day-to-day reproducibility by 7-fold, as seen by a 37–86% decrease in the coefficient of variation, compared to standard qPCR [ 315 ].…”
Section: Exosomes: a Source Of Tumor Biomarkersmentioning
confidence: 99%
“…Cellular proliferation is a critical aspect to tumor progression, which commonly is a result of the deregulation of cell-cycle related proteins [ 316 ], and is a known hallmark of cancer [ 22 ]. Research studies have demonstrated that tumor-derived exosomal miRNAs can regulate cancer cell proliferation by targeting cell cycle-associated proteins and signaling proteins [ 317 ]. For example, in colorectal cancer, miR-200b is transferred between adjacent cancer cells, where it directly targets 3′-UTRs of p27 and Rho Family GTPase 3 (RND3), two proteins involved in cell cycle regulation [ 318 , 319 ], leading to their downregulation, which in turn induces proliferation in recipient cells [ 320 ].…”
Section: Exosomes: a Source Of Tumor Biomarkersmentioning
confidence: 99%